2017
DOI: 10.1016/j.jand.2016.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Tribally Affiliated Child-Care Center Environment and Obesogenic Behaviors in Young Children

Abstract: Background Childcare centers are an integral part of life for many families with young children. American Indian children are at elevated health risk due to higher levels of obesity and associated health behaviors. Objective Assess the childcare environment and children’s physical activity (PA) and dietary intake in young children attending tribally-affiliated childcare. Design Cross-sectional study Participants/setting 11 tribally-affiliated childcare centers across Oklahoma and 82 three-to-five-year-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Accelerometry data were processed using 15-s epochs, and valid wear time was considered to be at least 10 h of wear time for at least 3days. Nonwear time was established by 30 min of continuous 0 count per minute (cpm) 36 . Established cut points were used to classify SB and TPA (light PA, moderate PA, and VPA) and VPA based on the criteria of Pate etal.…”
Section: Methodsmentioning
confidence: 99%
“…Accelerometry data were processed using 15-s epochs, and valid wear time was considered to be at least 10 h of wear time for at least 3days. Nonwear time was established by 30 min of continuous 0 count per minute (cpm) 36 . Established cut points were used to classify SB and TPA (light PA, moderate PA, and VPA) and VPA based on the criteria of Pate etal.…”
Section: Methodsmentioning
confidence: 99%
“…Parents were asked that the accelerometer be worn continuously (24 hours) for seven days, with an additional day for familiarization (total eight days), and only removed for water-based activities. Non-wear-time was considered 30 minutes or greater periods of continuous zeroes similar to other studies, 22,23 and these bouts were removed. The data were analyzed using age appropriate cut points for 15-second epochs including moderate-to-vigorous PA (MVPA) > 420 counts and 200 to 419 counts for light PA (LPA).…”
Section: Movement Behaviorsmentioning
confidence: 99%
“…Most of the studies exploring what children eat in childcare, have been conducted in childcare centers [24][25][26][27][28][29][30][31][32][33][34][35]. These studies found that there is room for improvement of their diet quality, in particular with regards to consuming high amounts of saturated fat, sodium, and added sugars [25,26,28,36].…”
Section: Introductionmentioning
confidence: 99%